EDTA Modified PANI/GO Composite Based Detection of Hg (II) Ions - Mahadik, Manasi; Patil, Harshada; Bodkhe, Gajanan; Ingle, Nikesh; Sayyad, Pasha; Al-Gahaouri, Theeazen; Shirsat, Sumedh M.; Shirsat, Mahendra (Frontiers in Materials, 2020)
Electrochemical recognition of Hg (II) ions utilizing EDTA modified polyaniline (PANI)/Graphene Oxide (GO) composite is reported in the present communication. Graphene Oxide (GO) synthesis was carried out by modified Hummer’s method. Electrochemical characterizations viz. cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) were done before and after modification of composite. Topography of PANI/GO composite and EDTA_PANI/GO electrodes was studied using AFM. Roughness parameter were compared for confirmation of surface modification. Fourier transform infrared spectroscopy (FTIR) was utilized for the compositional analysis of PANI/GO and EDTA_PANI/GO electrodes. The EDTA_PANI/GO composite shows sensitivity towards Hg (II) ions. It was identified using differential pulse stripping voltammetry (DPSV) technique with lower detection limit of 2 ppb. EDTA modified SS_PANI/GO composite (PANI/GO composite deposited on stainless steel substrate) have shown superior sensitivity in detection of Hg (II) ions. The sensitivity was observed upto 1 ppb which is smaller than maximum contaminant level (MCL) endorsed by Environment Protection Agency (EPA, USA).